Nitrous oxide in the atmosphere: First measurements of a lower thermospheric source. Issue 6 (16th March 2016) - Sheese, Patrick E.; Walker, Kaley A.; Boone, Chris D.; Bernath, Peter F.; Funke, Bernd
Abstract: Nitrous oxide (N2 O) is an important anthropogenic greenhouse gas, as well as one of the most significant anthropogenic ozone‐depleting substances in the stratosphere. The satellite‐based instrument Atmospheric Chemistry Experiment‐Fourier Transform Spectrometer has been observing the Earth's limb since 2004 and derives profiles of N2 O volume mixing ratios in the upper troposphere to the lower thermosphere. The resulting climatology shows that N2 O is continuously produced in the lower thermosphere via energetic particle precipitation and enhanced N2 O is present at all latitudes, during all seasons. The results are consistent with an N2 O production source peaking near or above 94 km via low‐energy particles, as well as a polar wintertime source near 70 km via medium energy particles. N2 O produced in the polar upper atmosphere descends each winter to as far down as 40 km. Key Points: ACE‐FTS first to observe N2 O production via energetic particle precipitation in lower thermosphere N2 O produced in mesosphere‐lower thermosphere descends into upper stratosphere during polar winter N2 O is not a good dynamical tracer in polar winter upper stratosphere